DEFINING A SUSTAINABLE TOURISM PERSPECTIVES IN EASTERN PART OF BALKHASH-ALAKOL BASIN - Rakhimzhanova GULNUR; Mussina KAMSHAT (Geo Journal of Tourism and Geosites)
This study focuses on the existing shortcomings of greening, absence of parks for long-term development of Eastern part of the Balkhash-Alakol Basin (Destination). We identifyed these issues through GIS analysis. And study aims to underline the importance of Destination's green development. We had done verification visually by radar and optical images by using GIS technology, as well as by field survey methods land surface cover with a wide homogeneous flatland and the absence of forest cover in the territory of the study Eastern part of the Balkhash-Alakol Basin. In addition, using GIS analysis we identified Destination's area growth from 944 to 1 437 square meters (in the period from 2013 to 2023). In order to define Destination's sustainable perspectives, we carried out regression analyses of air traffic of domestic and international destinations with the correlation of national currency to USD. Analyses show that regression reveals a 38.9% of error of prediction, indicating a moderate level of explanatory power in the model. This suggests that nearly 60 % of the variability in domestic air passenger numbers can be explained by the combination of international passenger volumes and fluctuations in the national currency rate (Tenge) to USD. Given the Destination's growth and the variability in domestic, international passenger numbers, it is necessary to create conditions for the development of Alternative Ecosystem Services in the form of specialized green parks, green lanes, and tourist pathways. This approach can lead to the creation of green areas and parks that not only provide recreational opportunities but also contribute to the conservation of biodiversity, cultural integrity and the overall well-being of the local community. Also, considering the existing environmental issues, an important perspective is to sustain the life cycle of the Destination in the stage of green development.